Lipid abnormalities in atopic dermatitis - Phongroop, Kannika (Veterinary Integrative Sciences, 2014)
The outermost layer of epiderm is as known Stratum corneum establishes skin barrier function. Stratum corneum is composed of lining up of many ﬂ attened corniocytes that adhere to each other by extracellular lipid lamellae (ELL). There are three major lipids components of ELL that are ceramides (CERs), chloresterol, and free fatty acid (FFA). Structural and function impairment of CERs represent in human and animal suffering with atopic dermatitis, cause of increasing transepidermal water loss (TEWL), increasing percutaneous invasive of environmental allergen, and easier to induce skin hypersensitivity reaction. Thus, skin barrier repair, especially additional topical CERs, is interesting in veterinarian now a day and may beneﬁ t to be an alternative treatment in canine atopic dermatitis.